SP0177 Partnership in action – how patient and professional organisations are working together in the uk. (1st June 2001) - Edwards, S
Abstract : Background: With the advent of patient empowerment and self-management, it is more important than ever that people with arthritis/rheumatism and those who treat them understand each others' needs and are able to work together. National organisations of patients and professionals have an important role to play in promoting partnership and mutual understanding. BLAR is an umbrella group which brings patient and professional organisations together to work for better services for people with arthritis/rheumatism in the UK. We have 23 Member organisations. We promote partnership and communication at a local and national level through a number of ways, for example: A multi-disciplinary project to agree and audit patient-centred standards of care. Establishing local networks of service users, health professionals and patient groups. Joint parliamentary lobbying for higher priority for arthritis/rheumatism. Joint policy development on issues of mutual concern. Workshops and meetings for service users and professionals to exchange information and best practice. Results: These projects have been very successful, and have demonstrated that partnership can be beneficial to both patient and professional organisations. We have also learned that by working together, we strengthen our voice. Partnership is not possible on every issue, and there will always be differences of opinion. However, we have succeeded in building lasting partnerships on key issues.